Selenium biofortification of soybean genotypes in a tropical soil via Se-enriched phosphate fertilizers - Silva, Maila Adriely; de Sousa, Gustavo Ferreira; Corguinha, Ana Paula Branco; de Lima Lessa, Josimar Henrique; Dinali, Guilherme Soares; Oliveira, Cynthia; Lopes, Guilherme; Amaral, Douglas; Brown, Patrick; Guilherme, Luiz Roberto Guimarães (Frontiers in Plant Science, 2022)
Soybean is a major crop in Brazil and is usually grown in oxidic soils that need high rates of phosphate (P) fertilizers. Soybean is also very suitable for biofortification with Se, since its grains have high protein contents and are widely consumed worldwide (directly or indirectly). Few studies have addressed Se application under field conditions for soybean biofortification, especially in tropical soils. Here, we evaluated agronomic and physiological responses resulting from different strategies for biofortifying soybean grains with Se by applying this element via soil, using both conventional and enhanced-efficiency P fertilizers as Se carriers. The experiment was carried out at the Uva Farm, in Capão Bonito (SP), Brazil. The experimental design was a RBD, with 4 fertilizer sources - conventional monoammonium phosphate (C-MAP), conventional monoammonium phosphate + Se (C-MAP + Se), enhanced-efficiency monoammonium phosphate (E-MAP), and enhanced-efficiency monoammonium phosphate + Se (E-MAP + Se) - and 4 soybean genotypes (M5917, 58I60 LANÇA, TMG7061, and NA5909). The selenium rate applied via C-MAP + Se and E-MAP + Se was 80 g ha-1. The application of the tested fertilizers was carried out at the sowing of the 2018/2019 cropping season, with their residual effect being also assessed in the 2019/2020 cropping season. Selenium application increased grain yield for the TMG7061 genotype. For all evaluated genotypes, Se content in grains increased in the 2018/2019 harvest with the application of Se via C-MAP + Se and E-MAP + Se. In general, the application of Se via C-MAP favored an increase in amino acid contents in grains and decreased lipid peroxidation. In summary, the application of Se-enriched P fertilizers via soil increased soybean grain yield, leading to better grain quality. No residual effects for biofortifying soybean grains were detected in a subsequent soybean cropping season.